(untitled) (Journal of Educational Sciences, 2017)
Synchronized swimming is the subjective sport and the victory at the Olympics depends on many factors. Synchronized swimming promotion and its further development in Kazakhstan is carried out through the joint efforts of the Ministry of Culture and Sports of the Republic of Kazakhstan and the public association «Water Sports Federation of the Republic of Kazakhstan» (PA «WSF»). However, despite all the difficulties caused by the absence of specialized databases relevant to the international requirements for size, depth, temperature regime, equipped with specialized musical equipment, underwater video shooting system, gym, acrobatic and dance halls for centralized training of the national team, the synchronized swimming team of Kazakhstan is represented on the international arena. The synchronized swimming team athletes’ physical development statistics considered during the pedagogical experiment. The experiment conducted at the Kazakh Research Institute of Sports of the Republic of Kazakhstan (KRIS). The anthropometric characteristics of synchronized swimming athletes were done during the experiment.